Elevated Hapln2 Expression Contributes to Protein Aggregation and Neurodegeneration in an Animal Model of Parkinson's Disease - Wang, Qinqin; Zhou, Qinbo; Zhang, Shuzhen; Shao, Wei; Yin, Yanqing; Li, Yandong; Hou, Jincan; Zhang, Xinhua; Guo, Yongshun; Wang, Xiaomin; Gu, Xiaosong; Zhou, Jiawei (Frontiers in Aging Neuroscience, 2016)
Parkinson’s disease (PD), the second most common age-associated progressive neurodegenerative disorder, is characterized by the loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SN). The pathogenesis of PD and the mechanisms underlying the degeneration of DA neurons are still not fully understood. Our previous quantitative proteomics study revealed that hyaluronan and proteoglycan binding link protein 2 (Hapln2) is one of differentially expressed proteins in the substantia nigra tissues from PD patients and healthy control subjects. However, the potential role of Hapln2 in PD pathogenesis remains elusive. In the present study, we characterized the expression pattern of Hapln2. In situ hybridization revealed that Hapln2 mRNA was widely expressed in adult rat brain with high abundance in the substantia nigra. Immunoblotting showed that expression levels of Hapln2 were markedly upregulated in the substantia nigra of either human subjects with Parkinson’s disease compared with healthy control. Likewise, there were profound increases in Hapln2 expression in neurotoxin 6-hydroxydopamine-treated rat. Overexpression of Hapln2 in vitro increased vulnerability of MES23.5 cells, a dopaminergic cell line, to 6-hydroxydopamine. Moreover, Hapln2 overexpression led to the formation of cytoplasmic aggregates which were co-localized with ubiquitin and E3 ligases including Parkin, Gp78 and Hrd1 in vitro. Endogenous α-synuclein was also localized in Hapln2-containing aggregates and ablation of Hapln2 led to a marked decrease in levels of α-synuclein in insoluble fraction compared with control. Thus, Hapln2 is identified as a novel factor contributing to neurodegeneration in PD. Our data provides new insights into the cellular mechanism underlying the pathogenesis in PD.